UPAYA PENINGKATKAN HASIL BELAJAR SISWA PADA PELAJARAN SENI BUDAYA ARANSEMEN MUSIK MANCANEGARA DENGAN MEDIA PEMBELAJARAN AUDIO VISUAL - Eni Sukmawati (Pedagogia: Jurnal Ilmiah Pendidikan, 2020)
EFFORTS TO IMPROVE STUDENT LEARNING OUTCOMES IN INTERNATIONAL MUSIC ARRANGEMENT CULTURAL ARTS LESSONS USING AUDIO VISUAL LEARNING MEDIA This research departs from the phenomenon that occurs in class, namely the lack of understanding of composing a song using audiovisual media. This study aims to (1) find out that audio visual learning media can improve student learning outcomes about international music arrangements. (2) To describe the process of improving student learning outcomes about International Music Arrangements before and after using audio-visual learning media. (3) To measure the magnitude of the increase in student learning outcomes about International Music Arrangements after using audio-visual learning media. Audio-visual learning media can improve student learning outcomes on International Music Arrangement material in SMA Negeri 9 Bogor.